2021
DOI: 10.1021/acs.jpcb.0c10834
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Structural and Spectroscopic Properties of LOV-Based Proteins with Improved Fluorescence

Abstract: Flavin-based fluorescent proteins are a class of fluorescent reporters derived from light, oxygen, and voltage (LOV) sensing proteins. Through mutagenesis, natural LOV proteins have been engineered to obtain improved fluorescence properties. In this study, we combined extended classical Molecular Dynamics simulations and multiscale Quantum Mechanics/Molecular Mechanics methods to clarify the relationship between structural and dynamic changes induced by specific mutations and the spectroscopic response. To rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Preliminary calculations (Table S1) performed at the ωB97XD/6-31+G­(d) level on the dark-AppA crystal structure showed that the first excited state (S 1 ) is a bright state corresponding to the first absorption band of the measured spectrum, whereas the next bright state which corresponds to the second observed band is S 3 . At this level of theory, the excitation energies of the two bands are significantly overestimated, as observed before, particularly for the second band. This also leads to overestimating the energy difference between the first two bands.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Preliminary calculations (Table S1) performed at the ωB97XD/6-31+G­(d) level on the dark-AppA crystal structure showed that the first excited state (S 1 ) is a bright state corresponding to the first absorption band of the measured spectrum, whereas the next bright state which corresponds to the second observed band is S 3 . At this level of theory, the excitation energies of the two bands are significantly overestimated, as observed before, particularly for the second band. This also leads to overestimating the energy difference between the first two bands.…”
Section: Resultssupporting
confidence: 65%
“…Between the TD-DFT methods, B3LYP shows the best agreement with experiments, but closer inspection showed that with this functional both bright states were strongly mixed with dark states. This issue was observed before, and it does not depend on the basis setall that finally encouraged us to employ ωB97X-D/6-31+G­(d) in subsequent calculations.…”
Section: Resultsmentioning
confidence: 74%
“…The long-range corrected ωB97X-D functional was chosen to avoid artificial mixing of the S 1 state, as found in our previous work on another flavoprotein. 55 This is extremely important in order to avoid an unphysical description of the excited-state potential energy surface.…”
Section: Methodsmentioning
confidence: 99%
“…The choice of the QM level was dictated by the need of a qualitatively correct description of ground and excited states, while at the same time limiting the computational cost. The long-range corrected ωB97X-D functional was chosen to avoid artificial mixing of the S 1 state, as found in our previous work on another flavoprotein . This is extremely important in order to avoid an unphysical description of the excited-state potential energy surface.…”
Section: Methodsmentioning
confidence: 99%
“…Figure displays their chromophore structures. iLOV is an engineered extrinsically fluorescent protein that binds the flavin mononucleotide (FMN). , bR is a light-driven transmembrane protein pump. Its retinal chromophore is covalently linked via a Schiff base to the protein backbone .…”
mentioning
confidence: 99%